Legal Protection for Contracting Parties Against Unilateral Termination of Government Construction Contracts - Muskibah Muskibah; Sasmiar Sasmiar; Evalina Alissa (JURNAL AKTA, 2026)
Unilateral termination in the implementation of government construction work contracts resulting in the position of the unilaterally terminated party who suffers a very weak loss, considering that there is no certainty regarding legal protection for the aggrieved party. In fact, the purpose of legal protection in contract law in particular is to restore the ownership or proprietary of the aggrieved party in the implementation of the agreement. This article aims to encourage the strengthening of regulations by reconstructing regulations regarding unilateral termination of government construction work contracts. Secondly, this article also examines the legal consequences of government construction work contracts that are unilaterally terminated, and how it affects both service users and service providers. The research method used is normative juridical research. The results of the study show that the unilateral termination clause regulated in the Law and in the Civil Code contains null and void conditions and overrides Article 1266 and Article 1267 of the Civil Code does not provide legal certainty and legal protection for the parties who enter into the contract, due to the reasons for the termination of the contract are not contained in the contract and do not meet the proper nullity requirements. The legal consequences of unilateral termination for both service users and service providers give rise to legal obligations that must be fulfilled by both parties.